2019
DOI: 10.3389/fgene.2019.00169
|View full text |Cite
|
Sign up to set email alerts
|

Blood Circulating miRNAs as Cancer Biomarkers for Diagnosis and Surgical Treatment Response

Abstract: miRNAs can function as potential oncogenes or tumor suppressors. Altered expression of these molecules was correlated with the occurrence of many cancer diseases and therefore they are considered a molecular tool for non-invasive cancer diagnosis and prognosis. We searched for analyses concerning expression of blood circulating miRNA in cancer patients. The studies comprised of at least two miRNA expression measurements: before and after the surgical therapy were considered. We summarized latest reports on eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 43 publications
1
75
0
Order By: Relevance
“…Differences in miR expression have not only been described in tissue biopsies, but also in blood samples of cancer patients [ 48 , 59 ]. As in tissues, some miRs have been proposed as potential blood biomarkers for cancer diagnosis and prognosis [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in miR expression have not only been described in tissue biopsies, but also in blood samples of cancer patients [ 48 , 59 ]. As in tissues, some miRs have been proposed as potential blood biomarkers for cancer diagnosis and prognosis [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs could change the inflammatory responses via the regulation of gene expression by post-transcriptional modifications that cause degradation and inhibition of the translation of the molecular target [18,19,24]. Recent studies have shown that mature miRNAs could be potential biomarkers for diagnosis in many human diseases such as cancers, cardiovascular disease, and neurodegenerative disease [25][26][27][28]. In a study of IPF, the changes of miRNAs were demonstrated in the analysis of miRNA arrays containing probes for 450 miRNAs with isolated RNA from the lungs from patients with IPF or the control [29].…”
Section: The Role Of Mirna In Ipfmentioning
confidence: 99%
“…However, several reports showed promising results that have not been confirmed in independent studies [ 7 ]. The application of circulating RNA molecules, including non-coding RNAs (ncRNAs), as biomarkers has been widely explored in the last few decades; miRNAs have been suggested as diagnostic biomarkers for several diseases, including neurodegenerative [ 8 , 9 ], neurodevelopmental [ 10 ], traumatic [ 11 ], neoplastic [ 12 , 13 ], and metabolic conditions [ 14 , 15 ]. Indeed, miRNAs have been detected in all analyzed biological fluids [ 16 , 17 , 18 ], making them useful as disease biomarkers measurable in all body districts.…”
Section: Introductionmentioning
confidence: 99%